Kalmyks of the Salsky district in the context of national politics and ethno-social processes in the 1920s - Anton Viktorovich Averyanov (Монголоведение)
Introduction. The most important task of the national policy of the Soviet state in the 1920s. There was an integration of ethnic minorities into the emerging socio-economic and cultural space. A unique situation developed in the Salsky district, where the Don Cossacks-Kalmyks, due to changed political conditions, lost their status as a leading social group, which led to their marginalization and required the development of new state policy approaches to involve them in the economic development of the region. The purpose of the article is to identify the features of ethno social relations in the Salsky district during the NEP period, to identify and analyze the key mechanisms of socio-political and economic integration of the Kalmyk population. The research was conducted on the basis of archival materials from the State Archive of the Russian Federation, as well as other archival documents and published sources. Results. The scale and nature of demographic changes in the Salsky district after the Civil War and during the NEP period were revealed. The changes in the role and place of Kalmyks in the economic structure of the district in comparison with German colonists and Russian peasants are shown. The features and specifics of the development of Kalmyk farms in the 1920s, their key problems and government support measures are highlighted. The main directions of national policy towards the Kalmyk population of the Salsky district in the field of economics, culture, education, and everyday life are analyzed. It is noted that despite the negative consequences of the Civil War, crop failures, and negative migration dynamics, the Don Kalmyks managed to preserve their ethno cultural identity. It was established that the key problem remained the land management of the Kalmyk population in conditions of land shortage, while maintaining the traditional pastoral nature of the economy for a significant part of the Kalmyks. It is proved that within the framework of its solution, a purposeful policy was pursued to popularize farming, develop cooperation, agricultural assistance, and concentrate the Kalmyk population in national village councils, which by the end of the 1920s were to become the main one for the formation of the Kalmyk National district. At the same time, within the framework of the indigenization policy, work was carried out to expand the network of schools, reading rooms, teacher training, and increase the level of literacy.